1990
DOI: 10.1007/bf00379064
|View full text |Cite
|
Sign up to set email alerts
|

Importance of exposure to gaseous and particulate phase components of tobacco smoke in active and passive smokers

Abstract: The uptake of tobacco smoke constituents from gaseous and particulate phases of mainstream smoke (MS), inhaled by smokers, and of environmental tobacco smoke (ETS), breathed in by non-smokers, was investigated in two experimental studies. Tobacco smoke uptake was quantified by measuring carboxyhemoglobin (COHb), nicotine and cotinine in plasma and urine and the data obtained were correlated with urinary excretion of thioethers and of mutagenic activity. An increase in all biochemical parameters was observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
3

Year Published

1991
1991
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 29 publications
3
41
0
3
Order By: Relevance
“…[11][12][13] Cigarette smoke acts in two ways: centrally and peripherally. Central action occurs when the smoker inhales on the cigarette.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Cigarette smoke acts in two ways: centrally and peripherally. Central action occurs when the smoker inhales on the cigarette.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that exposure to biofuels is associated with COHb levels of 2.5-13% (16,17), covering the range seen for passive through heavy active smoking (18,19). It is therefore not unreasonable to expect that the effect of passive smoking on birth weight would also apply to pregnant women habitually exposed to high levels of biofuel smoke, as is the case in developing countries (20,21).…”
Section: Tobacco Smoke Biofuels and Low Birth Weightmentioning
confidence: 99%
“…The influence of smoking on fertility, pregnancy and lactation Paulo Roberto Bezerra de Mello 1 , Gilberto Rodrigues Pinto 2 , Clovis Botelho 3 A fumaça do cigarro no ambiente é derivada de duas origens: fumaça central (FC) e fumaça periférica (FP). A fumaça central é formada quando o fumante traga o cigarro, é produzida com altas temperaturas, acima de 950ºC, e polui o ambiente após ter sido puxada através do cigarro, filtrada pelos pulmões do fumante e em seguida exalada 1-3. Essa é a fonte predominante de exposição dos fumantes ativos.…”
Section: Influência Do Tabagismo Na Fertilidade Gestação E Lactaçãounclassified